Advancing equity through strengthening research on health and well-being of Asian American, Native Hawaiian, and Pacific Islander - Dan Xi; Ming Lei; Paul Liu; Ramesh Vemuri; Yihong Ye (Cell & Bioscience, 2022)
Abstract The National Institutes of Health’s Asian American, Native Hawaiian and Pacific Islander Health Scientific Interest Group (NIH AANHPI-HSIG) provides a viewpoint on developing approaches to enhance research on health and wellbeing for Asian American, Native Hawaiian, and Pacific Islander ethnic populations, in order to advance racial equity amongst such populations.